Dielectric and dilatometric properties of Rb2ZnI4 and its mixed systems. (10th September 2018) - Yamaguchi, T.; Takashige, M.
Abstract: Rb2 ZnI4 shows phase transitional anomalies at about 4 K and about 62 K in the temperature dependence of the dielectric constant. To investigate those, the dielectric and dilatometric measurements were performed for the mixed systems (Rb1– x K x )2 ZnI4 and Rb2 Zn1– x Cd x I4 . In particular, the order of phase transitions was investigated as functions of concentration x, by measuring the discontinuous change of the linear thermal expansions with the clip-type strain-gauge dilatometer.